DEATH PENALTY IN DRUG CRIMES: Analysis of Constitutional Court Decisions from a Human Rights Perspective - Rahayu, Anisa Fuji; Sahara, Anisa; Chatlina, Chiara Belva; Putra, Muhammad Irsyad Irman; Sari, Puput Intan Permata; Mulyadi, Dedi (Indonesian Journal Publisher, 2026)
The application of the death penalty for narcotics crimes in Indonesia remains controversial because it involves a conflict between the state’s authority to impose criminal sanctions and the protection of the fundamental right to life guaranteed by the 1945 Constitution and international human rights instruments. This study aims to analyze the Constitutional Court’s legal reasoning regarding the constitutionality of the death penalty for narcotics crimes, examine international human rights perspectives, and evaluate its proportionality in modern criminal law. This research uses a normative juridical method with statutory, case, and conceptual approaches. The analysis is based on Constitutional Court decisions related to the Narcotics Law and relevant international human rights instruments such as the International Covenant on Civil and Political Rights (ICCPR). The results show that the Constitutional Court maintains the constitutionality of the death penalty by classifying narcotics crimes as extraordinary crimes, while emphasizing that its application must be limited as an ultimum remedium. However, international human rights standards increasingly criticize the death penalty for drug crimes because it does not meet the category of “most serious crimes.” This study concludes that although constitutionally permissible, the death penalty for narcotics crimes raises concerns regarding proportionality and compatibility with international human rights standards.